KAJIAN BERPIKIR KRITIS PADA METODE INKUIRI - Dwi Nugraheni Rositawati (Universitas Sebelas Maret, 2018)
Abstract: This study examines the fundamental things of the Inquiry Method that can be used to improve critical thinking skills. The purpose of this study are: a) Knowing the mechanism of the Inquiry Method can be used to improve critical thinking skills, b) Knowing the steps of critical thinking, c) Knowing the characteristics of critical thinking, d) Knowing the supporting components of the increasing critical thinking skills by applying inquiry method, and e) Knowing the role of supporting components and their influence in improving critical thinking skills by applying inquiry methods. The results of the study revealed that critical thinking consisted of six sub-abilities which became the core of critical thinking skills, namely interpretation, analysis, evaluation, inference, explanation, and self-regulation. The steps of the Inquiry method are the foundation for critical thinking and can be used as a